2015
DOI: 10.1074/jbc.m114.614719
|View full text |Cite
|
Sign up to set email alerts
|

Integrins Influence the Size and Dynamics of Signaling Microclusters in a Pyk2-dependent Manner

Abstract: Background:The mechanism by which integrin signaling regulates lymphocyte cytolytic activity is poorly understood. Results: The extent of integrin ligation influences the size and dynamics of signaling microclusters. Conclusion: Integrins regulate the magnitude and duration of proximal signaling that affect lymphocyte degranulation kinetics and the rate of target cell lysis. Significance: Integrin engagement ensures more rapid cytolytic granule release and faster target cell destruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 50 publications
4
25
0
Order By: Relevance
“…We suspect that the initial adhesion is due to cytoskeletal changes that occur as the CTL binds to ICAM-1 immobilized on the beads or plastic surface. Consistent with this, a recent study showed that NK adhesion to ICAM-1-expressing cells was reduced upon Pyk2 siRNA knockdown by ∼20-25% when examined at 20 min after conjugate formation (20), which could be due to the decreased mobility of microclusters (18). When the expression of a number of genes encoding proteins known to function upstream and downstream of Pyk2 was downregulated with siRNA, only knockdown of CasL blocked adhesion of NK cells (20).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…We suspect that the initial adhesion is due to cytoskeletal changes that occur as the CTL binds to ICAM-1 immobilized on the beads or plastic surface. Consistent with this, a recent study showed that NK adhesion to ICAM-1-expressing cells was reduced upon Pyk2 siRNA knockdown by ∼20-25% when examined at 20 min after conjugate formation (20), which could be due to the decreased mobility of microclusters (18). When the expression of a number of genes encoding proteins known to function upstream and downstream of Pyk2 was downregulated with siRNA, only knockdown of CasL blocked adhesion of NK cells (20).…”
Section: Discussionsupporting
confidence: 65%
“…In T cells, Pyk2 is critical for short-lived effector CD8 + T cell generation as well as adhesion on ICAM-1 substrates (17). More recently, it was demonstrated that inhibition of Pyk2 activity in NK-92 cells decreases the integrin-regulated mobility and displacement of the microclusters that form at the contact zone with a target cell (18).…”
mentioning
confidence: 99%
“…We have previously shown that MHC clusters on APC may include heterotypic membrane proteins such as ICAM-1, a ligand for LFA-1 integrin, which augment the sensitivity of the T cell response (1). This is consistent with our recent findings showing that integrinmediated signaling regulates the efficiency of proximal signaling in cytotoxic lymphocytes (46,47). Productive engagement of other receptors leads to recruitment of adaptor and signaling proteins to the TCR-containing clusters and formation of signalosomes (48) that integrate receptor-mediated signaling.…”
supporting
confidence: 90%
“…Prior to the polarization of the microtubule organizing center (MTOC) to the IS, lytic granules converge to the MTOC in a dynein-dependent minusended directed manner that is independent of actin polymerization and microtubule dynamics; as such, ligation of LFA-1 or CD28 alone is sufficient to induce convergence (19,20). LFA-1-mediated outside-in signaling leads to Factin polymerization and reorganization, phosphatidylinositol 4,5-bisphosphate (PtdIns(4,5)P2) generation, and the activation of protein tyrosine kinases, including Src family kinases (21,22). Activating signaling and sustained F-actin remodeling promotes the polarization of the MTOC, with converged lytic granules, to the lytic IS (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%